2017
DOI: 10.1103/physrevx.7.021047
|View full text |Cite
|
Sign up to set email alerts
|

Role of Water in the Selection of Stable Proteins at Ambient and Extreme Thermodynamic Conditions

Abstract: Proteins that are functional at ambient conditions do not necessarily work at extreme conditions of temperature T and pressure P. Furthermore, there are limits of T and P above which no protein has a stable functional state. Here, we show that these limits and the selection mechanisms for working proteins depend on how the properties of the surrounding water change with T and P. We find that proteins selected at high T are superstable and are characterized by a nonextreme segregation of a hydrophilic surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 37 publications
(90 citation statements)
references
References 96 publications
(182 reference statements)
2
88
0
Order By: Relevance
“…To perform this study we adopt a coarse-grained lattice representation of proteins which is computationally affordable and has been widely adopted in literature. [34][35][36][37][38][39][40][41] A protein is represented as a self-avoiding heteropolymer, composed of 20 amino acids. The residues interact through a nearest-neighbour potential given by the Miyazawa Jernigan interaction matrix.…”
Section: The Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To perform this study we adopt a coarse-grained lattice representation of proteins which is computationally affordable and has been widely adopted in literature. [34][35][36][37][38][39][40][41] A protein is represented as a self-avoiding heteropolymer, composed of 20 amino acids. The residues interact through a nearest-neighbour potential given by the Miyazawa Jernigan interaction matrix.…”
Section: The Methodsmentioning
confidence: 99%
“…We consider a series of native protein structures, and for each, we determine one or more sequences designed to make the protein fold into the aqueous environment. [34,35] Each sequence exhibits a different ratio between the number of hydrophilic amino acids exposed to the solvent and the number of hydrophobic amino acids buried into the core of the protein in its native conformation. For each protein, we study its capability to fold as a function of its concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, ice nucleation needs to be investigated as a function of different molecular properties, such as water-substrate interactions and surface morphologies. Most of the recently published computational studies of heterogeneous ice nucleation used the monoatomic coarse grained mW water model [47,48]. The fast dynamics of this simple water model and its numerical efficiency are the main reasons why current brute force simulation methods can be applied to the ice nucleation problem.…”
Section: The Importance Of Molecular Modeling For the Understanding Omentioning
confidence: 99%
“…The first evidence to support our claim comes from our previous work on heteropolymer design including the Caterpillar design Our work on design showed that provided that a heteropolymer chain is designable (we defined the rules to identify such property) then the 3D structures can be designed with high accuracy independently of the interaction matrix used to define the amino acid interactions . In fact, the same design strategy works for lattice and off‐lattice proteins with implicit or explicit solvent, plus the above mentioned patchy polymers . This result is the first indications that the key correlations that determine the folding do not depend on the particular model used to represent the residue interactions.…”
Section: Methodsmentioning
confidence: 99%
“…This result is the first indications that the key correlations that determine the folding do not depend on the particular model used to represent the residue interactions. The only requirement, of course, is that the protein structural space is correctly represented and for that, we can bring not only the evidence produced by the Caterpillar model it‐self but also made with its close cousins: the tube model of Maritan et al . and the CamTube model .…”
Section: Methodsmentioning
confidence: 99%